High Sleep Disturbance and Longer Concussion Duration in Repeat Concussions. Issue 2 (3rd March 2020) - Oyegbile, Temitayo Oyefunmike; Dougherty, Andrew; Tanveer, Sarah; Zecavati, Nassim; Delasobera, Bronson Elizabeth
ABSTRACT: Objectives : The relationship between repeated concussions and sleep disturbance is yet to be fully understood. The objective of this study was to examine the relationship between sleep disturbance, concussion duration, and repeated concussions by assessing postconcussive symptoms and cognition. Methods : Subjects (ages 13–33 years) underwent postconcussion cognitive function evaluation and reported postconcussion symptoms including severity of disturbed sleep (drowsiness, trouble falling asleep, sleeping more than usual, and sleeping less than usual), mood disturbance (sadness, irritability, nervousness, and emotional lability), and headache. Data on cognitive function and concussive symptoms were collected for 430 subjects after first concussion, 192 subjects after second concussion, and 118 subjects after three or more concussions. A subset of subjects (119) were monitored longitudinally to assess concussion duration. Analyses included group comparisons, regression, and correlation; data were adjusted for age and gender. Results : Sleep disturbance differed significantly by group (mean[SEM]: 1st concussion = 2.56[0.2]; 2nd concussion = 3.65[0.34]; 3+ concussions = 4.32[0.43]). Concussion history predicts concussion duration ( R 2  = 0.20, F [1, 116] = 27.33, p < 0.001). Furthermore, trouble falling asleep (β = 0.15) and sleeping less than usual (β = 0.15) predicted concussion duration ( R 2  = 0.062, F [1, 116] = 3.15, p = 0.047). Reported sleep disturbance after repeated concussions was higher in patients with higher headache ( F [2, 732] = 3.15, p = 0.043) and mood disturbance ( F [2, 733] = 3.35, p = 0.036) severity. In addition, after repeated concussions, the positive correlation between sleep disturbance and cognitive dysfunction strengthened. Conclusions : History of repeated concussion is associated with longer concussion duration and higher reported sleep disturbance. Furthermore, those with sleep disturbance after repeated concussion exhibit more severe headaches, mood disturbance, and cognitive dysfunction. Abbreviations: ImPACT: Immediate Postconcussion Assessment and Cognitive Assessment (ImPACT); this is a computer-based test that assesses an individual's cognitive function and cumulatively documents current concussion symptoms. PCSS: Post Concussion Symptom Scale; this scale assesses the severity of concussion symptoms. SPSS: Statistical Package for Social Sciences. This is a statistical software package.